The Relevant Factors in Promoting Reading Activities in Elementary Schools - Han-Chen Huang; Yao-Hsu Tsai; Shih-Hsiang Huang (International Journal of Evaluation and Research in Education (IJERE), 2015)
In order to help students absorb knowledge, schools often conduct readingactivities. Thorough planning and strategies, however, are needed to insurethe effect of reading promotions, and make them a deeply-rooted part of life.This study adopted the analytic hierarchy process (AHP) to discuss therelevant factors in promoting reading activities in elementary schools, as wellas how the reading activities should be pushed forward to increase students’interest in reading and help them form good reading habits. The resultsshowed that there are three key success factors in promoting readingactivities: (1) teachers’ emphasis on and implementation of reading activities;(2) the reading habits of parents and other family members; (3) teachers’professional knowledge and skills in guiding the students to read.